The Politics of integration : Caribbean sovereignty revisited - Gilbert-Roberts, Terri-Ann (Ian Randle Publishers KingstonJM, 2013)
Focuses on the way in which the political elites interpret sovereignty as well as the paradox of sovereignty. Examines the concepts of sovereignty and regionalism - the one representing a traditional symbol of governance and the other a contemporary development strategy is reviewed in order to support the construction of a special framework for the definition and analysis of regional governance. Reviews the historical evolution of the concept of sovereignty. Presents an empirical review of the evolution and functioning of CARICOM and Eastern Caribbean regional institutions between 1974 and 2012. Presents some conclusions about the legacy of the regional tradition of sovereignty and discusses prospects for change.